2022
DOI: 10.1038/s12276-022-00855-4
|View full text |Cite
|
Sign up to set email alerts
|

The updated role of exosomal proteins in the diagnosis, prognosis, and treatment of cancer

Abstract: Exosomes are vesicles encompassed by a lipid bilayer that are released by various living cells. Exosomal proteins are encapsulated within the membrane or embedded on the surface. As an important type of exosome cargo, exosomal proteins can reflect the physiological status of the parent cell and play an essential role in cell–cell communication. Exosomal proteins can regulate tumor development, including tumor-related immune regulation, microenvironment reconstruction, angiogenesis, epithelial–mesenchymal trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 141 publications
2
53
0
Order By: Relevance
“…In this context, the identification of subclasses of extracellular vesicles derived from cancer cells and microenvironmental components associated with well-defined pathological processes would allow them to serve as complementary biomarkers of circulating cfDNA and circulating tumor cells. In recent years, several studies have demonstrated the value of exosomes as cancer biomarkers, allowing longitudinal monitoring of tumor heterogeneity and early identification of cancer subtypes ( 154 , 155 ), as well as monitoring microenvironmental subversion ( 156 ), tumor progression and prognostic decisions ( 157 ), and response to therapy to tailor therapeutic interventions ( 158 , 159 ). Further developments in this field will bring us closer to the most important goal of providing personalized cancer care.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the identification of subclasses of extracellular vesicles derived from cancer cells and microenvironmental components associated with well-defined pathological processes would allow them to serve as complementary biomarkers of circulating cfDNA and circulating tumor cells. In recent years, several studies have demonstrated the value of exosomes as cancer biomarkers, allowing longitudinal monitoring of tumor heterogeneity and early identification of cancer subtypes ( 154 , 155 ), as well as monitoring microenvironmental subversion ( 156 ), tumor progression and prognostic decisions ( 157 ), and response to therapy to tailor therapeutic interventions ( 158 , 159 ). Further developments in this field will bring us closer to the most important goal of providing personalized cancer care.…”
Section: Discussionmentioning
confidence: 99%
“…AMACR (an enzyme a-Methylacyl-CoA racemase) is known to be elevated in PCa tissue, where, in urine, exosomes are validated as a biomarker for clinical use to detect PCa at initial biopsy [ 44 ]. Biting et al and Xinyi et al explained in detail the advantages of exosomes as a liquid biopsy and their application as a potential complement [ 45 , 46 ].…”
Section: Exosomementioning
confidence: 99%
“…With the recent development of isolation methods of exosomes and the applications of protein spectrum, the roles of exosome proteins in the diagnosis, prognosis, and treatment of diseases have been demonstrated in many medical fields, especially for cancer [4]. Exosomal proteins include (1) Membrane transport and fusion-related proteins, such as annexin (Anx II), Rab-GTPase, and heat shock proteins (HSPs), including Hsp60, Hsp70, and Hsp90; (2) Four-transmembrane cross-linked proteins, namely CD9, CD63, CD81, CD82, CD106, Tspan8, intercellular adhesion molecule-1 (ICAM-1); (3) Multi-vesicular bodies (MVBs)-related proteins, for instance, ALIX and TSG101; (4) Other proteins, like integrins, actin, and myosin [5].…”
Section: Exosome Proteinmentioning
confidence: 99%